Certifying Turkish Forests: A Path to Sustainable Forestry Practices - Durusoy, İdris and Türker, Mustafa Fehmi and Sıvacıoğlu, Ahmet and Akbulut, Sefa and Altunel, Arif Oğuz and Enez, Korhan and Sivrikaya, Fatih and Demirel, Döndü and Kara, Mehmet Erdal and Genç, Adem and Koç, Enüs and Şimga, Aslıhan and Öztürk, Sevgi (Academician Publishing Book DOI Portal, 2023)
-